2022
DOI: 10.3390/polym14163371
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Whey Protein Edible Coating Containing Fish Gelatin Hydrolysates on Physicochemical, Microbial, and Sensory Properties of Chicken Breast Fillets

Abstract: This study aims to research the impact of coatings containing whey protein (WP), fish gelatin hydrolysates (FGH), and both compounds together (WP + FGH) on the shelf-life of chicken breast fillets over the course of 16 days of cold storage (4 °C, 4-day intervals), as assessed by their physicochemical, microbiological, and sensory properties. Overall, cooking loss, pH value, total volatile base nitrogen, free fatty acids, peroxide value, and thiobarbituric acid reactive substances increased with storage time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…These bioactive compounds from lemon peel play a crucial role in inhibiting bacterial growth and reducing oxidative processes, thus contributing to the preservation and freshness of chicken meat (Maru et al, 2021). In the research by Sabzipour-Hafshejani et al (2022), a coating comprising whey protein and fish gelatin hydrolysates showed effective retention of the sensory quality of chicken. The combination of these components contributed to the reduction of total mesophilic aerobic bacteria (TMAB) counts in the samples.…”
Section: Meat and Seafoodmentioning
confidence: 99%
See 1 more Smart Citation
“…These bioactive compounds from lemon peel play a crucial role in inhibiting bacterial growth and reducing oxidative processes, thus contributing to the preservation and freshness of chicken meat (Maru et al, 2021). In the research by Sabzipour-Hafshejani et al (2022), a coating comprising whey protein and fish gelatin hydrolysates showed effective retention of the sensory quality of chicken. The combination of these components contributed to the reduction of total mesophilic aerobic bacteria (TMAB) counts in the samples.…”
Section: Meat and Seafoodmentioning
confidence: 99%
“…In the research by Sabzipour‐Hafshejani et al. (2022), a coating comprising whey protein and fish gelatin hydrolysates showed effective retention of the sensory quality of chicken. The combination of these components contributed to the reduction of total mesophilic aerobic bacteria (TMAB) counts in the samples.…”
Section: Applications Of Edible Films From Fwbpmentioning
confidence: 99%
“…Sabzipour-Hafshejani et al 159 prepared whey protein coating containing fish gelatin hydrolysates and evaluated its effect on the shelf-life of chicken breast fillets during 16 days under cold storage. They showed that the whey protein and fish gelatin hydrolysates coated samples had the TBARS levels of 1.03 and 1.05 mg MDA per kg, respectively on day 16 while uncoated chicken breast fillet samples had the highest TBARS levels (1.25 mg MDA per kg).…”
Section: Applications Of Bioactive Peptides As Functional Food Ingred...mentioning
confidence: 99%